Exposure assessment of infants and young children on selected Fusarium toxins - Jacek Postupolski; Andrzej Starski; Ewa Ledzion; Jolanta Kurpińska-Jaworska; Małgorzata Szczęsna (National Institute of Public Health - National Institute of Hygiene, 2019)
Background. Mycotoxins belong to substances harmful to human health. They are found mainly in cereal products and their preparations. In particular, infants and young children who consume cereal products, including porridge and gruel, are exposed to these substances. Objective. The aim of the study is to assess the exposure of infants and young children in Poland to micotoxins (ochratoxin A. deoxynivalenol, nivalenol, fumonisins B1 and B1, T-2 and HT-2 toxins) derived from cereal products intended for infants and children. Material and methods. Samples of products (302) were taken from all over the country in the following three years (2011, 2012 and 2013). HPLC-MS / MS method was used to determine the test compounds. Results. Using the HPLC-MS / MS method, the assessment of population exposure in Poland to mikototoxins (ochratoxin A, deoxynivalenol, nivalenol, fumonisins B1 and B1, T-2 and HT-2 toxins) derived from cereal products (porridge, gruel) intended for infants and small children. Samples (302) were taken from across the country over the next three years. The exposure values obtained in the average exposure scenario range from 0.2 to 3% compared to the reference toxicological parameters. Considering that in the case of infants and young children, the tested products constitute a quantitatively significant part of the balanced diet of these consumers, and the remaining groups of foodstuffs, including vegetable products. fruit and meat and dairy products do not contribute significant amounts of mycotoxins to the diet can be accepted. that the level of contamination of cereal products does not pose a significant risk to the health of consumers. In the case of high exposure, it did not exceed 10% of the reference values for deoxynivalenol and the sum of fumonisins B1 and B2. These values were assessed as not relevant for the exposure of infants and young children. In contrast, in the case of zearalenone, the high level of exposure corresponded to 36% of the value of tolerable daily intake (TDI), and for the sum of T-2 and HT-2 toxins, the value of 48% of tolerable daily intake. In both cases, the contribution of pollutants to the diet was significant, but still remained 2-3 times less than the tolerable daily intake. Given, that cereal products are the main source of these contaminants, it can be estimated that exceeding the TDI value in relation to the total diet of infants and young children is unlikely. Conclusions. The exposure values obtained in the average exposure scenario range from 0.2 to 3% compared to the reference toxicological parameters. In the case of zearalenone, the high level of exposure corresponded to 36% of the TDI value. and for the sum of T-2 and HT-2 toxins, 48% TDI. The contribution of pollutants to the diet in both cases was significant. however, it still remained 2-3 times less than the tolerable daily intake. Considering, that cereal products are the main source of these pollutants can be assessed. that exceeding the TDI value for the total diet of infants and young children is unlikely.